Circular ribosomal DNA plasmids transform Tetrahymena thermophila by homologous recombination with endogenous macronuclear ribosomal DNA. - Yu, G L (1988)
We transformed the ciliate Tetrahymena thermophila by microinjection of circular plasmids containing the ribosomal RNA gene (rDNA). In the somatic macronucleus of Tetrahymena, the rDNA is in the form of linear palindromic molecules. The rDNA molecules from the C3 strain have a replication advantage over rDNA from both B strain and the C3 rDNA mutant rmm1. We constructed two circular plasmids carrying replication origin sequences from C3 rDNA and a point mutation (Pmr) in the 17S rRNA gene that confers resistance to the antibiotic paromomycin. One plasmid contained a single complete copy of the rRNA gene and its flanking sequences, while the other had an additional rDNA origin of replication. In all B or rmm1 Tetrahymena cell lines transformed with the plasmids, rDNA sequences from the plasmid were found in palindromic rDNA molecules. In one transformant line, a small amount of the plasmid was also retained in a form with the original circular restriction map. Our results show that the plasmids underwent homologous recombination with one arm of the endogenous rDNA to give heteropalindromic rDNA, or with both arms of the palindrome to form homopalindromic rDNA. The resulting recombinant molecules were able to replace the recipient's original rDNA completely, providing strong evidence that C3 rDNA sequences in the donor DNAs confer a replication advantage over recipient rDNA. Thus microinjection of circular plasmids provides a method for replacement of an endogenous gene or gene fragment with exogenous sequences.